2017
DOI: 10.1089/jayao.2017.0011
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Adolescents and Young Adults with Cancer: Oncology Provider Perceptions of Adolescent and Young Adult Unmet Needs

Abstract: Few studies have assessed oncology providers' perceptions of adolescent and young adult (AYA) cancer patients' unmet needs. In this statewide survey (N = 91), we found that most providers recognize the financial, insurance, and late effects needs of their AYA cancer patients. However, employment, education, behavioral health, sexuality, and social and family issues were endorsed by less than half of providers as areas where AYAs needed assistance. Few providers felt that their AYA cancer patients had unmet nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Adolescent and young adult cancer patients have previously lamented the silence surrounding sexual and romantic domains in the health system and a recent Danish study showed that staff members reported more activity than young patients when asked how often sexuality was mentioned in outpatient clinics . Correspondingly, a survey among American oncologists revealed that less than half believed that AYA patients needed counselling on sexuality/intimacy/body image disturbances . Several studies have emphasized that young cancer patients request a direct, frank, and honest dialogue with health providers about all dimensions of their disease .…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent and young adult cancer patients have previously lamented the silence surrounding sexual and romantic domains in the health system and a recent Danish study showed that staff members reported more activity than young patients when asked how often sexuality was mentioned in outpatient clinics . Correspondingly, a survey among American oncologists revealed that less than half believed that AYA patients needed counselling on sexuality/intimacy/body image disturbances . Several studies have emphasized that young cancer patients request a direct, frank, and honest dialogue with health providers about all dimensions of their disease .…”
Section: Discussionmentioning
confidence: 99%
“…However, in our sample, only AYAs diagnosed as young adults discussed issues around fertility. We suspect that this could be a result of a potential lack of patient and provider education and communication on fertility issues, especially among younger AYA patients who may not be perceived as needing reproductive counseling [25]. In addition, the adolescents and emerging adults we interviewed were further on average from diagnosis than the young adults, which could potentially explain these differences as fertility concerns may be more salient for patients closer to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual health is a critical yet often overlooked aspect of care for AYAs with cancer, potentially compromising their physical health and quality of life. [45][46][47] Specifically, sexual health refers to one's state of well-being in relation to one's sexual identity, preferences, behavior, and relationships. During adolescence and young adulthood, exploring sexuality, romantic relationships, and psychosexual identity are important aspects of development.…”
Section: Addressing Aya Sexual Health: Awareness Sensitivity and Dementioning
confidence: 99%
“…Although AYAs with cancer desire and benefit from receiving sexual health information, 46,63,64 clinicians do not consistently recognize sexual health as an unmet need. 46 Many also lack confidence in querying sexual/gender identity and providing appropriate care focused on sexual health.…”
Section: Addressing Aya Sexual Health: Awareness Sensitivity and Dementioning
confidence: 99%
See 1 more Smart Citation